Crystal structure and cytotoxic activities of a bis(pyrrolyl-imine) gold(III) complex. Issue 18 (16th September 2016) - Profirio, Daniel De Moraes; Paiva, Raphael Enoque Ferraz De; Abbehausen, Camilla; Cuin, Alexandre; Masciocchi, Norberto; Machado, Daisy; Lancellotti, Marcelo; Corbi, Pedro Paulo; Formiga, André Luiz Barboza
Abstract: A gold(III) complex with N, N′-ethylenebis(pyrrol-2-yl-methyleneamine) (H2 pyren) was synthesized and characterized by physicochemical and spectroscopic measurements. Density functional theory (DFT) studies and cytotoxic assays were performed. Infrared, mass spectrometry, and 1 H, 13 C, and 15 N, 1 H nuclear magnetic resonance analyses indicate that pyren is deprotonated and gold(III) is four coordinate in a square planar environment, with the pyrrole and imine nitrogens as donors. The structure was confirmed by powder X-ray diffraction and confirmed as a minimum of the potential energy surface by DFT. Cytotoxic activity of [Au(pyren)] + was active against three tumorigenic cell lines with IC50 values of 35 μM. Interaction studies with CT-DNA by fluorescence and competition with ethidium bromide (EB) showed a quenching of the emission band of DNA with a Stern–Volmer quenching constant value of (3.0 ± 0.1) × 10 4 M −1 and a decrease in fluorescence quenching of EB-DNA system, respectively, confirming that DNA is a possible target for the complex via an intercalative binding, which was confirmed by DNA conformational changes observed with circular dichroism spectroscopy. Abstract :